Identification of candidate genes associated with resistance to bruchid (Callosobruchus maculatus) in cowpea - Miesho, Belay; Malinga, Geoffrey M.; Ongom, Patrick Obia; Rubaihayo, Patrick; Kyamanywa, Samuel (Plant Breeding, 2019)
Cowpea is an important legume crop widely grown in sub-Saharan Africa for food and feed. However, it is largely challenged by bruchid, a serious storage pest resulting in losses in quantity and quality of grains. Therefore, this research was designed to contribute to the breeding of cowpea resistance to bruchid through the identification of candidate genes associated with resistance to bruchid. A total of 217 mini-core cowpea accessions were genotyped and phenotyped for their reactions to bruchid. To determine the genomic regions linked with bruchid resistance, 41,948 polymorphic SNP markers were used. Genome-wide association study identified 11 SNPs linked to the average number of eggs, holes, insect emergence and development period and Dobie susceptibility index. Gene search via Phytozome identified six candidate genes (Vigun08g132300, Vigun08g158000, Vigun06g053700, Vigun02g131000, Vigun01g234900 and Vigun01g201900) associated with the resistance traits. These candidate genes could be incorporated into the farmers preferred but susceptible cowpea varieties to bruchid. The SNP markers associated with the resistance traits can be used in marker-assisted breeding for accurate and rapid screening of cowpea resistant genotypes to bruchid.